HLA-E⁎01:03 Allele in Lung Transplant Recipients Correlates with Higher Chronic Lung Allograft Dysfunction Occurrence. (17th July 2016) - Di Cristofaro, Julie; Pelardy, Mathieu; Loundou, Anderson; Basire, Agnès; Gomez, Carine; Chiaroni, Jacques; Thomas, Pascal; Reynaud-Gaubert, Martine; Picard, Christophe
Abstract : Lung transplantation (LTx) is a valid therapeutic option for selected patients with end-stage lung disease. HLA-E seems to play a major role in the immune response to different viral infections and to affect transplantation outcome, in Hematopoietic Stem Cell Transplantation, for example. Two nonsynonymous alleles, HLA-E ⁎ 01:01 and HLA-E ⁎ 01:03, have functional differences, involving relative peptide affinity, cell surface expression, and potential lytic activity of NK cells. The aim of this retrospective study was to determine the impact of these two alleles for LTx recipients on anti-HLA alloimmunization risk, overall survival, and chronic rejection (CLAD). HLA-E was genotyped in 119 recipients who underwent LTx from 1998 to 2010 in a single transplantation center. In univariate analysis, both HLA-E homozygous states were associated with impaired overall survival compared to heterozygous HLA-E alleles (p = 0.01 ). In multivariate analysis, HLA-E ⁎ 01:03 allele showed increased CLAD occurrence when compared to homozygous HLA-E ⁎ 01:01 status (HR: 3.563 (CI 95%, 1.016–12), p = 0.047 ). HLA-E allele did not affect pathogen infection or the production of de novo DSA. This retrospective study shows an uninvestigated, deleterious association of HLA-E alleles with LTx and requires verification using a larger cohort.